Market Design with Correlated Valuations - Yongmin Chen; Ruqu Wang (Queen's University, Department of Economics, 2005)
The effects of information on market design are explored in a simple setting where firms have private information about their correlated fixed costs and the government aims to maximize its expected revenue conditional on achieving efficient allocations. Government revenues are higher when the costs are less correlated (or are more of a private value). The reduced correlation increases the firms' information rents, but a change in the information structure also changes the expected market structures with positive effects on government revenues. If the government faces the no-deficit constraint, there are situations where efficient allocations are achieved under asymmetric information but not under symmetric information.
Keywords: D4; L1; H8; 330; market structure; correlated values; market design; government revenue